Prognostic significance of tympanosclerotic plaques localization and their morphological and histological characteristics for the outcome of surgical treatment - Milojević Milanko; Đerić Dragoslava; Bijelić Dušan (Vojnosanitetski Pregled)
Background/Aim. Tympanosclerosis is a sequela of inflammation of the middle ear usually causing conductive hearing loss. The aim of the study was to determine the significance of tympanosclerotic plaques localization in the middle ear and their morphological and histological characteristics for surgical treatment outcome. Methods. This retrospective study included a total of 73 patients operated on for tympanosclerosis in the Clinic for Otorhinolaryngology, Military Medical Academy (MMA) in a period 1996-2010. The results of surgical treatment as well as the last audiometry findings were analyzed. considering follow-up periods of 6 months to 8 years. The patients were divided into 4 groups according to tympanosclerotic plaques localization in the middle ear and the classification suggested by Wieling and Kerr. The patients were also divided based on intraoperatively noticed morphological characteristics of tympanosclerotic plaques, while the third division was done as per histological findings. Surgical success was assessed using the suggestions of the Japan Otological Society. Results. The analyzed results showed the surgical success especially in the group II according to Wieling and Kerr, while histological findings had no impact on the outcome of the surgery. Conclusion. Surgical treatment has good results especially in patients with the mobile stapes. Results are satisfactory in other localizations, while various morphological and histological characteristics do not have impact on the surgery outcome.